A novel method to identify Post‐Aire stages of medullary thymic epithelial cell differentiation. Issue 2 (15th September 2020) - Ferreirinha, Pedro; Ribeiro, Camila; Morimoto, Junko; Landry, Jonathan J. M.; Matsumoto, Minoru; Meireles, Catarina; White, Andrea J.; Ohigashi, Izumi; Araújo, Leonor; Benes, Vladimir; Takahama, Yousuke; Anderson, Graham; et al.
Abstract: Autoimmune regulator + (Aire) medullary thymic epithelial cells (mTECs) play a critical role in tolerance induction. Several studies demonstrated that Aire + mTECs differentiate further into Post‐Aire cells. Yet, the identification of terminal stages of mTEC maturation depends on unique fate‐mapping mouse models. Herein, we resolve this limitation by segmenting the mTEC hi (MHCII hi CD80 hi ) compartment into mTEC A/hi (CD24 − Sca1 − ), mTEC B/hi (CD24 + Sca1 − ), and mTEC C/hi (CD24 + Sca1 + ). While mTEC A/hi included mostly Aire‐expressing cells, mTEC B/hi contained Aire + and Aire − cells and mTEC C/hi were mainly composed of cells lacking Aire. The differential expression pattern of Aire led us to investigate the precursor‐product relationship between these subsets. Strikingly, transcriptomic analysis of mTEC A/hi, mTEC B/hi, and mTEC C/hi sequentially mirrored the specific genetic program of Early‐, Late‐ and Post‐Aire mTECs. Corroborating their Post‐Aire nature, mTEC C/hi downregulated the expression of tissue‐restricted antigens, acquired traits of differentiated keratinocytes, and were absent in Aire‐deficient mice. Collectively, our findings reveal a new and simple blueprint to survey late stages of mTEC differentiation. Abstract : Although the expression of Aire was initially considered to mark a terminal stage of mTEC maturation, recent studies have demonstrated that mTECs extend their differentiation beyond Aire. Integrating flow cytometry, functional, and transcriptomic analyses, Ferreirinha et al. provide an effective phenotypic‐based method to resolve Early‐, Late‐ and Post‐Aire mTECs.